GENERATOR POHON KEPUTUSAN DENGAN MENERAPKAN ALGORITMA C4.5 UNTUK PROGRAM KONSULTASI - Irma Kharis; Rosa Delima; Joko Purwadi (Universitas Kristen Duta Wacana, 2013)
C4.5 algorithm is used to simplify decision tree from decision table by generating decision tree from an existing decision tree. With this algorithm, knowledge base in the decision table can be simplified. This research will build a consultation program using C4.5 algorithm which is called decision tree generator. Decision tree generator provides inference facility and a user interface for consultation. The user is required to build a knowledge base first, and the application will generate user interface automatically. There are two steps in decision tree generator: firstly, the application will build the decision tree, and after that the application will build the user interface for consultation session. The results of this research show that the decision tree generator can get goal and advice from tree exploration in consultation session.